The Performance Analysis of High-Rise Building Structure Based on SNI 03-1726-2012 and SNI 03-1726-2019 (Case Study: Tower 1 Transit-Oriented Development Apartment Pondok Cina, Depok) - Sudarno Tampubolon; Pinondang Simanjuntak; Gracela P. Tarapandjang; I Putu Ellsa Sarassantika (Journal of Infrastructure Planning and Engineering, 2023)
Indonesia has the latest seismic standard, namely SNI 03-1726-2012 which replaces the previous seismic standard, namely SNI 03-1726-2012. This study aims to compare the calculation and analysis of the result of the Transit-Oriented Development (TOD) apartment in Pondok Cina, Depok based on SNI 03-1726-2012 and SNI 03-1726-2019 and find out what parameters make a significant difference between SNI 03-1726-2012 and SNI 03-1726-2012. SNI 03-1726-2019. From the comparison results, there was an increase in the parameter values ​​of SS and S1 in SNI 03-1726-2019, resulting in the influence of the parameter values ​​of SDS and SD1 which became the reference for calculating the acceleration value of the response spectra in SNI 03-1726-2019. The value of the basic static shear force in the X and Y directions in SNI 03-1726-2019 increased by 18% from the value of the basic static shear force in SNI 03-1726-2012 and the value of the dynamic basic shear force in the X and Y directions in SNI 03-1726- 2019 experienced an increase of 15% from the value of the dynamic base shear force in SNI 03-1726-2012. The basic shear force increases because the acceleration spectral design response has a high increase in 03-1726-2019 compared to SNI 03-1726-2012. Based on the control of the performance level of the Transit-Oriented Development (TOD) apartment building, Pondok Cina Depok, is included in the Immediate Occupancy, meaning that when an earthquake occurs, the building does not suffer heavy damage, can still be used and the risk of casualties is very small. Performance-based planning can provide information on how the building behaves during an earthquake and the extent to which the earthquake will affect the structure.